Novel Ferrocenyl Methyl Î²-Diketone Complexes with Potent Antimicrobial Properties and Cytotoxicity - Hossen, M Faruk; Al-Bari, M Abdul Alim; Hossain, M Masem; Chowdhury, MK Basar; Zakaria, Chowdhury M; Islam, M Anwar Ul (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Key words: Ferrocenyl complexes; Antimicrobial activities; Cytotoxic properties Bangladesh j. genet. biotechnol. 7(1&2): 65-702006 (June & December)